Measurement of the B-0 Production Cross Section in pp Collisions at root s=7 TeV - Chatrchyan, S. (2011)
Measurements of the differential production cross sections d sigma/dp(T)(B) and d sigma/dy(B) for B-0 mesons produced in pp collisions at root s = 7 TeV are presented. The data set used was collected by the CMS experiment at the LHC and corresponds to an integrated luminosity of 40 pb(-1). The production cross section is measured from B-0 meson decays reconstructed in the exclusive final state J/psi K-S(0), with the subsequent decays J psi -> mu(+)mu(-) and K-S(0) -> pi(+)pi(-). The total cross section for p(T)(B) > 5 GeV and |y(B)| < 2: 2 is measured to be 33.2 +/- 2.5 +/- 3.5 mu b, where the first uncertainty is statistical and the second is systematic.